If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = n + -21 Reorder the terms: -6 = -21 + n Solving -6 = -21 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -6 + -1n = -21 + n + -1n Combine like terms: n + -1n = 0 -6 + -1n = -21 + 0 -6 + -1n = -21 Add '6' to each side of the equation. -6 + 6 + -1n = -21 + 6 Combine like terms: -6 + 6 = 0 0 + -1n = -21 + 6 -1n = -21 + 6 Combine like terms: -21 + 6 = -15 -1n = -15 Divide each side by '-1'. n = 15 Simplifying n = 15
| 180=3x-1+9x-7+19 | | 2(2y+6)+2y=12 | | 6h+4-3+6h=11 | | (2y-64)+(2y)=180 | | (7y^3-3y^2+4y)+(8y^4+3y^2)= | | 2x+5=9+3x | | (1-2x)=-2-(3+x) | | 3(r-4)=12 | | 0.7x+16+4w=27.28 | | 50=-6x+4x-3-8 | | 186=-6(5-4x)+3x | | 5y-8-3y+12= | | 8x+78=2x+3 | | x^3-a=0 | | C*4=20 | | j-(-18)=94 | | 180-70= | | Q+6=36 | | 15m=1.25 | | lnx^4-7lnx=1 | | (17n^4+2n^3)-(10n^4+n^3)= | | 22.41*2-5.09= | | 2x=10+2x | | logx+log(x+2)=log(3x) | | 10n+7-3n+5= | | (n+6)=(3n-10) | | -480=-8(4-7r) | | (-5)9x-15=-465 | | 5-3x+8x=6-2x+3x | | -x^2-6x-10=-1 | | f(x)=2tanx | | 4n-2-7n=20 |